HISTORICAL LINES IN DEVELOPMENT OF THE DEPARTMENT FOR COMMODITY RESEARCH AND EXPERTISE IN THE PLEKHANOV RUSSIAN UNIVERSITY OF ECONOMICS - Maria A. Nikolaeva; Tamara G. Rodina; Lyudmila G. Eliseeva; Petr P. Gorozhanin (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article shows history of establishing Moscow Commercial Institute, the first economics higher education institution of Russia. The authors depict historical stages in the development of the Department for Commodity Research and Expertise from its setting-up in 1908 to the present day. The article introduces founders of Russian academic commodity research, trends in the field of commodity research of food and non-food goods, shows Department academics in public life of the country and their scientific and consultative assistance to manufacturing and trade organizations. Today’s teaching process was assessed.